Reproducibility of the Obtained Centric Relation Records in Patients with Disc Displacement with Reduction - Samir Čimić; Sonja Kraljević Šimunković; Ana Savić Mlakar; Sunčana Simonić Kocijan; Petra Tariba; Amir Ćatić (University of Zagreb. School of Dental Medicine, 2018)
Objective: The aim of this study was to investigate reproducibility of the position of centric relation in patients with disc displacement with reduction. Materials and methods: The test group included 30 subjects, diagnosed with disc displacement with reduction in right, left or both joints. The control group included 12 individuals with no signs and symptoms of temporomandibular disorders. Using chin point guidance with a jig, centric relation record was made three times by every participant, in a single session. Left and right condylar position for each centric relation record was determined and recorded using the electronic ultrasonic measuring device. The data were transferred to the computer, processed and analyzed. Condylar distances between centric relation records were measured (anteroposterior, vertical, transversal and linear values), and the data were statistically analyzed using the t and the F tests. Results: No statically significant difference was found between the test and the control groups. Two thirds of study participants demonstrated condylar position of the repeated centric relation recording within the area of 0.3 mm in diameter. For more than 90% of participants that area was within 0.4 mm. Conclusions: There is no difference in reproducibility of the centric relation between patients with disc displacement with reduction and healthy temporomandibular joint individuals (p>0.05). When doing centric relation record on a patient with disc displacement with reduction there is no need for previous splint therapy and standard precautions are acceptable. The obtained results must be interpreted within the experimental group, and not projected on the other groups of temporomandibular disorders.